2018
DOI: 10.1080/21645515.2018.1526589
|View full text |Cite
|
Sign up to set email alerts
|

Maternal vaccine knowledge in low- and middle-income countries—and why it matters

Abstract: Maternal vaccines have the potential to reduce the global burden of neonatal morbidity and mortality by accessing the infant immune system before a vaccine administered in childhood would be effective. Maternal vaccines for influenza, tetanus, and pertussis have been shown to reduce neonatal disease and mortality, and other candidate vaccines for group B streptococcus and respiratory syncytial virus are being developed to continue this trend. However, safe and effective maternal vaccines will only successfully… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 24 publications
4
31
0
Order By: Relevance
“…30 For maternal vaccines, knowledge of vaccines among pregnant women has been shown to be an important driver of uptake in various settings. 16 In this study, reported refusal of vaccines was very uncommon; however, among the small number (n = 26) that had refused a vaccine, lack of sufficient information was the most common reason for refusal provided. Thus, even in a setting where pregnant women are relatively knowledgeable about vaccines, it is important to ensure that adequate and appropriate information is shared about maternal vaccines.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…30 For maternal vaccines, knowledge of vaccines among pregnant women has been shown to be an important driver of uptake in various settings. 16 In this study, reported refusal of vaccines was very uncommon; however, among the small number (n = 26) that had refused a vaccine, lack of sufficient information was the most common reason for refusal provided. Thus, even in a setting where pregnant women are relatively knowledgeable about vaccines, it is important to ensure that adequate and appropriate information is shared about maternal vaccines.…”
Section: Discussionmentioning
confidence: 65%
“…13 Lower levels of education, lack of knowledge on vaccination during pregnancy and other socioeconomic factors like high parity and low income have been identified as barriers to maternal vaccination in low-and middle-income countries (LMICs); however data on maternal vaccine acceptance from African settings are very limited. 4,[14][15][16] TT is the most widely implemented vaccine among pregnant women in LMIC. 14 In 2012, however, the WHO recommended that countries considering initiation or expansion of seasonal influenza vaccination give the highest priority to pregnant women, 17 and in 2015 noted that maternal vaccination against pertussis is likely to be the most costeffective way to prevent the disease in infants too young for vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal knowledge, attitudes, and beliefs about vaccines are an integral part of the underlying mechanisms of vaccine hesitancy. Understanding these factors will allow public health practitioners to design more effective interventions (Williams et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…More research would be needed, mainly in non-western, middle and low income countries, where different cultural and social factors may play a role in the acceptance of vaccination. 2,56,57 Generalizability is also limited by the fact that different tools were used across studies to assess hesitancy, knowledge and attitudes, few of which were validated prior to their use 45,46,58 : the same concepts may therefore have been measured by different items, making the results not fully comparable across studies and consequently not allowing the combination results in a quantitative synthesis. In this regard, Larson et al have stressed that many vaccine studies assess trust in vaccinations mainly through single-item measures, leaving an implicit definition of trust, indicating that a thorough understanding of trust as it relates to vaccine acceptance is currently under-researched.…”
Section: Discussionmentioning
confidence: 99%